Effectiveness and efficacy of nutritional therapy: A systematic review following Cochrane methodology. Issue 4 (August 2017) - Muscaritoli, Maurizio; Krznarić, Zeljko; Singer, Pierre; Barazzoni, Rocco; Cederholm, Tommy; Golay, Alain; Van Gossum, André; Kennedy, Nicholas; Kreymann, Georg; Laviano, Alessandro; Pavić, Tajana; Puljak, Livia; et al.
Summary: Background & aims: Disease-related malnutrition has deleterious consequences on patients' outcome and healthcare costs. The demonstration of improved outcome by appropriate nutritional management is on occasion difficult. The European Society of Clinical Nutrition and Metabolism (ESPEN) appointed the Nutrition Education Study Group (ESPEN-NESG) to increase recognition of nutritional knowledge and support in health services. Methods: To obtain the best available evidence on the potential effects of malnutrition on morbidity, mortality and hospital stay; cost of malnutrition; effect of nutritional treatment on outcome parameters and pharmaco-economics of nutritional therapy, a systematic review of the literature was performed following Cochrane methodology, to answer the following key questions: Q1) Is malnutrition an independent predictive factor for readmission within 30 days from hospital discharge? Q2) Does nutritional therapy reduce the risk of readmission within 30 days from hospital discharge? Q3) Is nutritional therapy cost-effective/does it reduce costs in hospitalized patients? and Q4) Is nutritional therapy cost effective/does it reduce costs in outpatients? Results: For Q1 six of 15 identified observational studies indicated that malnutrition was predictive of re-admissions, whereas the remainder did not. For Q2 nine randomized controlled trials and two meta-analyses gave non-conclusive results whether re-admissions could be reduced by nutritional therapy. Economic benefit and cost-effectiveness of nutritional therapy was consistently reported in 16 identified studies for hospitalized patients (Q3), whereas the heterogeneous and limited corresponding data on out-patients (Q4) indicated cost-benefits in some selected sub-groups. Conclusions: This result of this review supports the use of nutritional therapy to reduce healthcare costs, most evident from large, homogeneous studies. In general, reports are too heterogeneous and overall of limited quality for conclusions on impact of malnutrition and its treatment on readmissions.